Phemie Keller - Riddell, J. H., Mrs., 1832-1906 (Salt Lake City, UT : Project Gutenberg, 2023)
"Phemie Keller: a novel, vol. 1 of 3" by Mrs. J. H. Riddell is a work of fiction likely written in the mid-19th century. The novel explores themes of beauty, isolation, and human connection through the character of Captain Henry Gower Stondon, who finds himself entangled in the quiet life and complicated emotions of the inhabitants of Tordale Valley, particularly the enchanting Phemie Keller. The story is set against the backdrop of the picturesque yet rugged Cumberland hills, hinting at both the allure and the constraints of rural life. The opening of the novel introduces Captain Stondon, who travels to Tordale and is immediately captivated by the scenic beauty surrounding a secluded church. His reflections on life and death reveal a sense of longing and melancholy that permeates his existence as a wanderer. Upon attending a service, he is struck by the voice of Phemie Keller, a young woman of remarkable beauty and talent, whom he observes with keen interest. As the narrative unfolds, Stondon grapples with his feelings while navigating the dynamics of the local community, particularly regarding Phemie's status and prospects, which are complicated by her familial background and the expectations set upon her by her relatives. The stage is set for a poignant exploration of love, societal roles, and the tension between aspiration and reality as the characters' lives become increasingly intertwined. (This is an automatically generated summary.)
Release date is 2023-08-06
Richard Tonsing and the Online Distributed Proofreading Team at https://www.pgdp.net (This file was produced from images generously made available by The Internet Archive)
Keywords: Married women -- Fiction; Man-woman relationships -- Fiction; England -- Social life and customs -- Fiction; Spouses -- Fiction; May-December romances -- Fiction